Recent trends in miRNA therapeutics and the application of plant miRNA for prevention and treatment of human diseases - Atiyabanu N. Saiyed; Abhay R. Vasavada; S. R. Kaid Johar (SpringerOpen, 2022)
Abstract Background Researchers now have a new avenue to investigate when it comes to miRNA-based therapeutics. miRNAs have the potential to be valuable biomarkers for disease detection. Variations in miRNA levels may be able to predict changes in normal physiological processes. At the epigenetic level, miRNA has been identified as a promising candidate for distinguishing and treating various diseases and defects. Main body In recent pharmacology, plants miRNA-based drugs have demonstrated a potential role in drug therapeutics. The purpose of this review paper is to discuss miRNA-based therapeutics, the role of miRNA in pharmacoepigenetics modulations, plant miRNA inter-kingdom regulation, and the therapeutic value and application of plant miRNA for cross-kingdom approaches. Target prediction and complementarity with host genes, as well as cross-kingdom gene interactions with plant miRNAs, are also revealed by bioinformatics research. We also show how plant miRNA can be transmitted from one species to another by crossing kingdom boundaries in this review. Despite several unidentified barriers to plant miRNA cross-transfer, plant miRNA-based gene regulation in trans-kingdom gene regulation may soon be valued as a possible approach in plant-based drug therapeutics. Conclusion This review summarised the biochemical synthesis of miRNAs, pharmacoepigenetics, drug therapeutics and miRNA transkingdom transfer.